Grand corruption and government change: an analysis of partisan favoritism in public procurement - David-Barrett, Elizabeth (European journal on criminal policy and research, 2020)
Incoming governments sometimes abuse their power to manipulate the allocation of government contracts so as to buy loyalty from cronies. While scandals suggest such practices are relatively widespread, the extent of such partisan favoritism is difficult to measure and the conditions under which it flourishes under-theorized. Drawing on theory regarding the role of institutions as constraints on corruption, we identify three spheres of political influence over government contracting and show how elites can manipulate two of those spheres to increase their opportunities to influence the procurement process and minimize external accountability, facilitating the corrupt allocation of contracts to partisan allies. Using an innovative big data methodology, we then identify the effects of a change in government on procurement markets in two countries, Hungary and the United Kingdom, which differ in terms of political influence over these institutions. We find that politically-favored companies secure 50-60% of the central government contracting market in Hungary but only 10% in the UK.